Pediatric genitourinary tumors: Distribution, demographics, and outcomes - Azadeh Nazemi; Siamak Daneshmand; Andy Chang (Wiley, 2022)
ABSTRACT Importance The diversity of pediatric genitourinary malignancies requires a timely resource detailing tumor characteristics and survival. Objective To determine the incidence, demographics, and outcomes of all pediatric genitourinary tumors within the United States. Methods A population‐based search for patients diagnosed with genitourinary cancers under age 15 was performed using the National Cancer Institute's Surveillance, Epidemiology, and End Results 18 registry. Information on primary tumor location, histologic type, patient age, sex, year of diagnosis, race, treatment, cause of death, and survival months was extracted. Descriptive epidemiological and survival statistics were calculated for all variables. Results A total of 4576 cases from 1973 through 2015 were identified. The most common primary tumor sites were the kidney (80.3%), testis (12.3%), bladder (2.8%), and vagina (1.5%). Nephroblastoma (87.9%) and sarcoma (3.4%) were the most common renal malignancies. Rhabdomyosarcoma was common in the vagina, bladder, and testis at rates of 66.2%, 61.2%, and 24.6%, respectively. Germ cell tumors (71.0%) were the most common primary tumor of the testis. Ten‐year overall survival (OS) for renal nephroblastoma and sarcoma was 88% and 82%, respectively. Ten‐year OS for RMS of the testis was 91%, the bladder was 79%, the vagina was 79%, and the prostate was 56%. Germ cell tumor 10‐year OS were 96% in the testis and 100% in the vagina. Interpretation A better understanding of the overall distribution and outcomes associated with pediatric genitourinary cancers allows physicians to best understand the patient's disease in the context of current frequency in a genitourinary setting and reported outcomes.